Probable Rivaroxaban-Induced Full Body Rash: A Case Report. (October 2018) - Sasson, Evan; James, Marian; Russell, Mark; Todorov, Darko; Cohen, Henry
Introduction: Rivaroxaban is a novel oral anticoagulant with several indications, one of which is for stroke prevention in nonvalvular atrial fibrillation. We present a case of probable rivaroxaban-induced rash. Case Summary: A 79-year-old female with a medical history of atrial fibrillation experienced a stroke, after which she was prescribed rivaroxaban 20 mg. After several days, she developed a rash requiring admission to the emergency department and several days of treatment. The rash resolved and she was switched from rivaroxaban to apixaban and did not experience any adverse drug events. Discussion: Onset of symptoms occurred within days of rivaroxaban initiation. The patient had no allergy history and never reported a similar reaction while on concurrent home medication regimen. The resolution of rash and toleration of apixaban suggest a rivaroxaban-specific reaction. The mechanism of this rash is currently unclear. Conclusion: We report one of the first cases of probable rivaroxaban-induced rash, whereas the patient tolerated apixaban. Further investigation is warranted, but prescribers should be cognizant of this potential issue when choosing a factor Xa inhibitor for anticoagulation.